2016
DOI: 10.1088/0957-0233/27/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Application of the differential Fabry–Perot interferometer in angle metrology

Abstract: A differential Fabry-Perot interferometer (DFPI) was applied for the detection of ultra-small angles in the level of nanoradian (nrad) precision. During application, down to 1 nrad angular steps were generated using the available high precision small angle generator (HPSAG) and these steps were detected using the frequency stabilised lasers as an alternative and outperforming method to conventional angle interferometers. The use of the DFPI provided the displacement measurements (further angular displacements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The developed displacement system and proposed method will be used for calibration and comparison with highresolution displacement sensors which are used in dimensional metrology. The method will find direct application in longrange angle measurements with nanoradian uncertainties [18] as well as nanometre and sub-nanometre position control in semiconductor manufacturing processes [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The developed displacement system and proposed method will be used for calibration and comparison with highresolution displacement sensors which are used in dimensional metrology. The method will find direct application in longrange angle measurements with nanoradian uncertainties [18] as well as nanometre and sub-nanometre position control in semiconductor manufacturing processes [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Many methods exist for measuring angles using interferometry (for some examples see [8][9][10][11]). The angle interferometer we have built is a standard Twyman-Green interferometer (figure 1) that uses phase-stepping interferometry to create phase maps of the surface under test.…”
Section: Angle Interferometermentioning
confidence: 99%
“…Recently, there has been a push to provide NMI traceability for measurement of small angles [14], partly driven by the extreme, small angle measurement requirements for x-ray mirrors deployed at synchrotron light and free electron laser (XFEL) sources [15,16]. The European Metrology Research Programme project 'SIB58 Angles' [17] made progress in addressing these requirements: for example, Celik et al [18] demonstrated the measurement of nanoradian (nrad) steps using a differential Fabry Perot interferometer, based on a linear interferometer [19].…”
Section: Small-angle Generatorsmentioning
confidence: 99%